2010
DOI: 10.1007/s00421-010-1387-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate intensity resistance training during weight loss on body composition and physical performance in overweight older adults

Abstract: The impact of resistance training has not been thoroughly examined in overweight older adults undergoing weight loss. Subjects (n = 27) were overweight and obese (BMI 31.7 +/- 3.6 kg/m(2)) older (age 67 +/- 4 years) adults and were randomized into either a 10-week Dietary Approaches to Stop Hypertension for weight loss diet (DASH, n = 12) or DASH plus moderate intensity resistance training (DASH-RT, n = 15). Outcomes included weight loss, total body and mid-thigh composition, muscle and physical function. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
120
3
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 46 publications
5
120
3
7
Order By: Relevance
“…This results in a condition known as sarcopenia obesity, or a loss of muscle mass that occurs as a result of obesity and because of natural aging. The study done by Avila et al [28] examined the effects of diet alone on lean mass, and also included a diet plus resistance training group to be used as a comparison group to the diet alone group. The study consisted of 27 older obese adults with an average age of 67 (± 4) years.…”
Section: Diet and Older Adultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This results in a condition known as sarcopenia obesity, or a loss of muscle mass that occurs as a result of obesity and because of natural aging. The study done by Avila et al [28] examined the effects of diet alone on lean mass, and also included a diet plus resistance training group to be used as a comparison group to the diet alone group. The study consisted of 27 older obese adults with an average age of 67 (± 4) years.…”
Section: Diet and Older Adultsmentioning
confidence: 99%
“…Diet alone results in weight loss, improved physical function, and the DASH diet also significantly improves blood pressure measures. Previous studies [31,32,33] have shown that diet combined with exercise actually yields the greatest results in physical function, blood pressure, and can also influence weight loss [26,28]. Exercise and diet combined can result in weight loss and minimize loss of lean muscle, as well as improving physical function.…”
Section: Dash Diet and Older Adultsmentioning
confidence: 99%
See 3 more Smart Citations